Atomistic modeling of hydrogen embrittlement at grain boundaries of Mg - L. Liu; L.N. Li; X. Liu; X.D. Shu; C. Xie (Journal of Materials Research and Technology)
Magnesium is a competitive candidate material for engineering lightweight structures and biomedical degradable scaffolds. However, it often suffers unpredictably sudden failure in atmospheric and physiological environments. The prevailing viewpoints have indicated that the failure is closely related to hydrogen. So far, the relevant hydrogen-induced damage mechanisms are still of significant controversy. Building an Mg–H atomic system and conducting molecular dynamics (MD) simulations, this study quantitatively investigates the possibility of hydrogen segregation at grain boundaries (GBs) and reveals the trend of critical energy release rate (CERR) for fracture at the matrix and GBs with increasing hydrogen concentration of single-crystal and polycrystalline systems. The results show that hydrogen tends to segregate at GBs due to GB energy providing more trapping sites. The CERRs for cracking both at the matrix crystal planes and GBs significantly decrease with increasing hydrogen concentration owing to metallic bond weakening, and GBs become more brittle than crystal planes. In the systems without hydrogen, there is a higher tensile strain at fracture, the growth of the free surface is usually accompanied by dislocation emission, and the cracks can even propagate along the migrated GBs with a higher misorientation angle, resulting in an uneven fracture surface with void coalescence features. The tensile stress-strain curves of the systems with high hydrogen concentration exhibit a significant low-stress rapid unloading characteristic. As the hydrogen concentration increases, the dislocation density decreases significantly and the free surface rapidly grows along the hydrogen-distributed crystal planes or GBs, resulting in a smooth fracture surface with cleavage features.